Focal and bidirectional modulation of lower limb motor cortex using anodal transcranial direct current stimulation - Sangeetha Madhavan (Brain Stimulation, 2010)
Background: Because we are interested in noninvasive transcranial brain stimulation as an adjuvant to poststroke walking therapy, we applied transcranial direct current stimulation (tDCS) preferentially to either the left or right lower limb motor cortex (M1) in two separate sessions and assessed the resulting modulation in both cortices. Objective: We hypothesized that tDCS applied preferentially to one lower limb M1 of healthy subjects would induce between-hemisphere opposite sign modulation. Methods: Transcranial magnetic stimulation (TMS) with the coil offset 2 cm either side of vertex was used to assess the percentage of change in the rectified motor-evoked potential (MEP) area recorded bilaterally from the vastus lateralis (VL) and tibialis anterior (TA) of 10 subjects during weak tonic contraction. Results: Analysis of variance (ANOVA) revealed an up-regulation of the target cortex and a down-regulation of the nontarget cortex (P=.001) and no effects of hemisphere (left, right) or muscle (TA, VL). Significant modulation was evident in 78% of VL and TA muscles (all P < .05). Excitability increased in 60%, but decreased in 18%. For 43% when excitability increased, a simultaneous decrease in excitability was evident in homologous muscle responses providing support for our hypothesis. Conclusions: The results indicate a modest effectiveness and focality of anodal tDCS when applied to lower limb M1, suggesting in a human model that the strength and depth of polarizing cortical currents induced by tDCS likely depend on interindividual differences in the electrical properties of superficial brain structures.